2001
DOI: 10.1590/s0066-782x2001000700001
|View full text |Cite
|
Sign up to set email alerts
|

Use of transesophageal echocardiography during implantation of aortic endoprosthesis (stent). Initial experience

Abstract: The use of transesophageal echocardiography during placement of aortic stents seems appropriate. The actual advantages of the procedure will be defined in a comparative prospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…Intravascular ultrasound (IVUS) has been used to in a similar fashion [45-47]. Both TEE and IVUS can also be used to measure aortic diameters and location of the great vessels, site of injury etc [43, 46, 48]. …”
Section: Diagnosismentioning
confidence: 99%
“…Intravascular ultrasound (IVUS) has been used to in a similar fashion [45-47]. Both TEE and IVUS can also be used to measure aortic diameters and location of the great vessels, site of injury etc [43, 46, 48]. …”
Section: Diagnosismentioning
confidence: 99%
“…The most common IVFB is a fragment of central venous catheter [6], but CTA didn't confirm this hypothesis and showed no retrograde extension of the initial dissection. TEE was performed because of its high ability in diagnosing diseases of the thoracic aorta and for excluding structural defects/imperfections of the endoprosthesis patency [12].…”
Section: Resultsmentioning
confidence: 99%
“…According to our experience, multidisciplinary approach with meticulous quality control is mandatory [12][13][14] as well as collaboration between all clinicians. Per-operative communication is crucial, even in emergency conditions.…”
Section: Resultsmentioning
confidence: 99%
“…12 Initial studies have shown that TEE monitoring is promising also during stent-graft positioning in type B aortic dissection. [9][10][11] However, all previous studies represent initial experience in a limited number of patients (10-16 patients in larger studies), and a systematic comparison between angiography and TEE was not performed. This is the first large study to evaluate the additional value of TEE to fluoroscopy and angiography.…”
Section: Discussionmentioning
confidence: 99%
“…Transesophageal echocardiography (TEE) provides superior diagnostic accuracy for aortic dissection with respect to angiography, [6][7][8] and initial limited studies showed that TEE may be useful during positioning of stent grafts. [9][10][11] We sequentially applied angiography and TEE to guide intraoperative decision-making in our patients routinely re-ferred for stent-graft implantation to treat type B aortic dissection. Herein we compare the contributions of TEE and angiography, and evaluate the usefulness of a TEEbased algorithm developed to guide decision-making during implantation of stent grafts in aortic dissection.…”
mentioning
confidence: 99%